2017
DOI: 10.1177/0300060517722698
|View full text |Cite
|
Sign up to set email alerts
|

Oral paracetamol versus oral ibuprofen for treatment of patent ductus arteriosus

Abstract: ObjectiveThis study was performed to investigate the safety and efficacy of oral paracetamol versus oral ibuprofen in the treatment of patent ductus arteriosus (PDA) in premature infants.MethodsPremature infants with PDA with a gestational age of ≤32 weeks or birth weight of ≤1500 g were included in this randomized study.ResultsA total of 120 premature infants fulfilled the inclusion criteria. Of these 120 infants, 34 fulfilled the treatment criteria and 22 were finally randomized. We found no significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 26 publications
2
33
0
7
Order By: Relevance
“…This difference may allow POX inhibition to be optimally effective under conditions of low COX inhibitory activity (20). To date, although a number of correlative randomized controlled trials (RCTs) have compared the therapeutic efficacies of paracetamol and other drugs for PDA closure, most achieved insignificant results (21)(22)(23)(24)(25). Paracetamol's efficacy and safety for PDA closure in premature or low-birth-weight infants (or both) have not been fully determined.…”
Section: Introductionmentioning
confidence: 99%
“…This difference may allow POX inhibition to be optimally effective under conditions of low COX inhibitory activity (20). To date, although a number of correlative randomized controlled trials (RCTs) have compared the therapeutic efficacies of paracetamol and other drugs for PDA closure, most achieved insignificant results (21)(22)(23)(24)(25). Paracetamol's efficacy and safety for PDA closure in premature or low-birth-weight infants (or both) have not been fully determined.…”
Section: Introductionmentioning
confidence: 99%
“…Rate of ductus closure was 100%, with no adverse events reported. In subsequent years, additional case series and clinical trials evaluating this new treatment option have been published (7,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Table 1 summarizes the existing randomized clinical trials (RCTs) comparing paracetamol to standard treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A summary of the studies' designs are compiled in Table 3. 8,[11][12][13][14][15][16] Outcomes from all studies were similar in that paracetamol was equally effective in closing PDA as compared to ibuprofen or indomethacin. Adverse effects observed varied from study to study.…”
Section: Resultsmentioning
confidence: 89%
“…In the studies by Oncel et al, 13 Al-Lawama et al, 14 and Dash et al, 15 paracetamol was associated with a similar rate of adverse reactions as ibuprofen and indomethacin. In contrast, Bagheri et al, 8 Balachander et al, 11 Dang et al, 12 and El-Mashad et al 16 reported the relative safety of paracetamol, in that it was associated with significantly lower rates of various adverse events such as acute kidney injury, thrombocytopenia, hyperbilirubinemia, gastrointestinal bleeding, liver or renal dysfunction, intraventricular haemorrhage, and retinopathy of prematurity.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation